Functional and taxonomic dynamics of an electricity-consuming methane-producing microbial community. (November 2015) - Bretschger, Orianna; Carpenter, Kayla; Phan, Tony; Suzuki, Shino; Ishii, Shun'ichi; Grossi-Soyster, Elysse; Flynn, Michael; Hogan, John
Highlights: Electromethanogenic reactors demonstrated reproducible trends for 6 months. Functional correlations found between phyla Desulfovibrionaceae and Euyarcheota . Electromethanogenic enrichments are extremely sensitive to open-circuit conditions. Abstract: The functional and taxonomic microbial dynamics of duplicate electricity-consuming methanogenic communities were observed over a 6 months period to characterize the reproducibility, stability and recovery of electromethanogenic consortia. The highest rate of methanogenesis was 0.72 mg-CH4 /L/day, which occurred during the third month of enrichment when multiple methanogenic phylotypes and associated Desulfovibrionaceae phylotypes were present in the electrode-associated microbial community. Results also suggest that electromethanogenic microbial communities are very sensitive to electron donor-limiting open-circuit conditions. A 45 min exposure to open-circuit conditions induced an 87% drop in volumetric methane production rates. Methanogenic performance recovered after 4 months to a maximum value of 0.30 mg-CH4 /L/day under set potential operation (−700 mV vs Ag/AgCl); however, current consumption and biomass production was variable over time. Long-term functional and taxonomic analyses from experimental replicates provide new knowledge toward understanding how to enrich electromethanogenic communities and operate bioelectrochemical systems for stable and reproducible performance.